Geochemistry and microbiology of boreal alluvial soil under salinisation - Khayrulina, E.A.; Mitrakova, N.V.; Maksimov, A.Yu; Maltseva, P.Yu; Bogush, A.A. (Geoderma Regional, 2024)
Soil salinisation in taiga landscapes is in most cases caused by anthropogenic activities. The study was carried out in Perm region (Russia) on the territory of the Verkhnekamskoe Potash Deposit. The inflow of sodium chloride drainage water into ground and surface waters during the production of potash fertilisers contributed to the technogenic salinisation of river valleys in the taiga zone. The purpose of the research was to investigate the microbial composition and chemical properties of alluvial soils in the area affected by NaCl waters in the Lyonva River valley. The chemical properties of soils were determined standard methods such as potentiometric method, titration, and spectrophotometry. The microbial community was determined by 16 s rRNA gene metagenomic analysis. The soil's mineralogical composition was determined using a binocular microscope and diffractometer for XRD. The morphology and microstructure of the samples has been studied using an analytical scanning electron microscope. In Solonchaks, an interdependence of salinity and bacterial species composition was discovered, along with the bacteria's geochemical processes. The topsoil contains a considerable amount of toxic salts, ranging from 5.9 to 17%. The ratio of exchangeable cations in the soil absorption complex changes when exchangeable calcium is replaced by sodium. Salinisation caused the neutralisation of acidic alluvial soils. Bacteria originating from marine and highly mineralised environments predominate in the soil. The soils are dominated by bacteria originating from marine and highly mineralised environments, such as Proteobacteria, Shewanella (75–79%), Thiomicrospira (26%), Desulfuromonas, Marinomonas and Idiomarina (9–10%), Alicyclobacillus (4%). The correlation revealed the connection of some taxa with ions of aqueous extract, as well as with exchangeable sodium, mobile iron and total sulphur. Some bacteria promote azonal geochemical processes within alluvial forest soil, such as the reduction of iron and manganese, the production of sulphides, and the oxidation of sulphur, hydrogen, and iron. Sulphide accumulation resulting in the formation of a hydrotroilite horizon (FeS × nH2O) and iron-bearing formations were found on the soil surface. Studying the properties and degree of soil disturbance makes it possible to identify the contribution of enterprises to environmental pollution, as well as to apply new methods for monitoring, purifying, and storing potassium waste.